MIRZO ULUGBEK IS THE FOUNDER OF THE TIMURID RENAISSANCE (Scientific journal of the Fergana State University, 2024)
Eastern scientific-philosophical thinking, which is a component of the spiritual heritage of the peoples of the world, has been attracting constant attention for centuries as universal spiritual values. The global study of the philosophical views of the Timurid period, which is an important component of the scientific and philosophical thinking of the East, is of great importance for understanding the essence of the second renaissance period in the East. In the history of world philosophy, research is being conducted to study the development of the philosophical thinking of the Timurid era. The scientific-theoretical study of the socio-philosophical ideas of the thinkers of the Timurid era from the point of view of the requirements of the present time is of great importance in forming a high spiritual image in young people and raising them morally. In this article, Eastern and Western scientists who contributed to the development of the science of astronomy, their spiritual heritage, the life of the ruler and astrologer Mirzo Ulugbek, scientific and creative activities, madrasas, observatories, and the spiritual life of scholars who worked with the thinker A number of scholars who scientifically researched the heritage are discussed.